Developmental outcome of the use of etamsylate for prevention of periventricular haemorrhage in a randomised controlled trial. Issue 1 (21st December 2004) - Schulte, J; Osborne, J; Benson, J W T; Cooke, R; Drayton, M; Murphy, J; Rennie, J; Speidel, B
Abstract : Objective: To compare neurodevelopmental outcome of survivors of the multicentre trial of etamsylate (the iRNN for ethamsylate) for prevention of periventricular haemorrhage in very low birthweight infants. Design: Double blind, single observer, prospective follow up of placebo controlled study. Setting: Six neonatal intensive care units in the United Kingdom. Neurodevelopmental outcome was assessed in health premises or children's homes. Subjects: 268 of 276 survivors of the original study were seen between 3.5 and 4.2 years of age. All were inborn and weighed 1500 g or less at birth. Intervention: Etamsylate 12.5 mg/kg or placebo six hourly from within one hour of delivery for four days. Main outcome measures: McCarthy scales of children's abilities, standardised neurological examination, full physical examination, functional assessment, seven letter Stycar vision test, and audiometry. Results: There was no difference between the groups in neuromotor outcome (cerebral palsy) or in the general cognitive index (GCI) of the McCarthy scales (mean GCI was 93.3 for the etamsylate group (n = 133) and 89.7 for the placebo group (n = 131); p = 0.10). There were more children with GCI < 70 (9 v 19; p = 0.047) or ⩽ 50 (3 v 11; p = 0.03) in the placebo group. Fewer children in the etamsylate group had squints (17 v 30; p = 0.042) or required surgery for patent ductus arteriosus (1 v 8; p = 0.036). Conclusions: Etamsylate was not associated with a reduction in cerebral palsy. Severe cognitive impairment was reduced, but more children died and the improvement may be because fewer survived with low GCI.